Genetics of Lithium Response in Bipolar Disorder - Papiol, Sergi; Schulze, Thomas G.; Alda, Martin (Pharmacopsychiatry, 2018)
Introduction Lithium remains the best-established long-term treatment for bipolar disorder because of its efficacy in maintaining periods of remission and reducing the risk of suicide. Not all patients successfully respond to lithium treatment, and the individual response, including the occurrence of side effects, is highly variable and not easy to predict. The genetic basis of lithium response is supported by the fact that the response clusters in families. Likewise, recent high-throughput genomic analyses have shed light on its genetic architecture.Methods This nonsystematic review summarizes the main results obtained in genetic association studies using lithium response as target trait.Results These studies suggest that several genetic loci might modulate the way a patient responds to lithium maintenance treatment. Further studies to fully characterize the genetic architecture of lithium response are warranted.Discussion The identification of genetic factors associated with lithium response will be important for (1) better understanding of lithium’s mode of action and (2) development of a predictive model for optimization of long-term treatment of bipolar disorder.
Keywords: bipolar disorder treatment; genetics; bipolar disorder